2020
DOI: 10.1080/15332640.2020.1836702
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative exploration of the experiences of men who use drugs of obtaining psychoactive medicinal products in Jordan

Abstract: In Jordan, almost any medication can be bought from pharmacies. This ready availability is linked with abuse. Previous literature describes medicine abuse from pharmacists' and general public perspectives. Here we investigate experiences of 17 men in addiction treatment in Amman (21-39 years) of obtaining psychoactive medicines. Alprazolam, clonazepam, bromazepam and tramadol were most commonly abused. Psychoactive medicines were obtained from street dealers, but pharmacies were preferred. Regulations appears … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…In this study, participants reported that they faced no problem accessing the treatment centers during the pandemic either by ambulance or phone, the fact that may have mitigated the adverse consequences. None of the participants mentioned online interventions during the pandemic, which is consistent with previous studies from lowmiddle income countries (LMICs) (Arjadi et al, 2015;Wazaify et al, 2020). In other countries, programmatic adaptations to COVID-19 SUD care, including telehealth and loosening restrictions around medications for opioid use disorders mitigated the difficulties that patients had faced, especially among low-income individuals with SUD (Zhen-Duan et al, 2022).…”
Section: (Participant 14 45 Years Old)supporting
confidence: 83%
“…In this study, participants reported that they faced no problem accessing the treatment centers during the pandemic either by ambulance or phone, the fact that may have mitigated the adverse consequences. None of the participants mentioned online interventions during the pandemic, which is consistent with previous studies from lowmiddle income countries (LMICs) (Arjadi et al, 2015;Wazaify et al, 2020). In other countries, programmatic adaptations to COVID-19 SUD care, including telehealth and loosening restrictions around medications for opioid use disorders mitigated the difficulties that patients had faced, especially among low-income individuals with SUD (Zhen-Duan et al, 2022).…”
Section: (Participant 14 45 Years Old)supporting
confidence: 83%